2015
DOI: 10.1055/s-0035-1555655
|View full text |Cite
|
Sign up to set email alerts
|

An International Multicenter Study Assessing the Role of Ethnicity on Variation of Lumbar Facet Joint Orientation and the Occurrence of Degenerative Spondylolisthesis in Asia Pacific: A Study from the AOSpine Asia Pacific Research Collaboration Consortium

Abstract: Study Design A multinational, multiethnic, cross-sectional image-based study was performed in 33 institutions, representing 10 countries, which were part of the AOSpine Asia Pacific Research Collaboration Consortium. Objective Lumbar facet joint orientation has been reported to be associated with the development of degenerative spondylolisthesis (DS). The role of ethnicity regarding facet joint orientation remains uncertain. As such, the following study was performed across a wide-ranging population base to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
0
26
0
2
Order By: Relevance
“…The facet joints were found to be increasingly irregular, flat and significantly narrowed as the dimensions of the endplate defects increased. Facet joints are the point of contact between adjacent neural arches of the vertebral bodies and small changes in postural angle can lead to high stress concentration . It may be possible that endplate damage and resulting uneven stress distribution and disc degeneration cause much of the compressive stress to pass through the neural arch affecting the facet joints .…”
Section: Discussionmentioning
confidence: 99%
“…The facet joints were found to be increasingly irregular, flat and significantly narrowed as the dimensions of the endplate defects increased. Facet joints are the point of contact between adjacent neural arches of the vertebral bodies and small changes in postural angle can lead to high stress concentration . It may be possible that endplate damage and resulting uneven stress distribution and disc degeneration cause much of the compressive stress to pass through the neural arch affecting the facet joints .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the facet angle consistently increased from L2-L3 to L5-S1 with regards to the sagittal plane [7]. However, it has also been demonstrated that the L4-5 and L5-S1 facet joints have high variations in facet angle depending on ethnicity [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the difference in the results for the facet joint orientation at the L5–S1 in the healthy population between our study and Grobler's might be explained by the difference in age of the two study populations. Williams et al [8] reported an average facet joint orientation at the L5–S1 of 43.3°±13.0° for the left and 43.1°±12.5° for the right lumbar facet joints in patients with degenerative spondylolisthesis in a multicenter study in the Asia-Pacific region. The difference in the results for the facet joint orientation at the L5–S1 between our study and Williams et al's might be explained by the presence of degenerative spondylolisthesis and difference in the age of the two study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Facet joint orientation in the sagittal plane has been reported to be from 150° to 170° from the vertical axis with no differences between each lumbar level [2]. In contrast, facet joint orientation in the horizontal plane has been reported as having 10° to 15° of standard deviation in Caucasian and African–American bone models [2] and patients with spondylolisthesis in Asia-Pacific legion [8], which suggests a wide variation between individuals. Furthermore, facet joint orientation in the horizontal plane changes toward the sagittal direction with aging [69].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation